2004
DOI: 10.1086/381092
|View full text |Cite
|
Sign up to set email alerts
|

GB Virus Type C Coinfection in HIV‐Infected African Mothers and Their Infants, KwaZulu Natal, South Africa

Abstract: GB virus type C (GBV-C) infection was studied in a convenience sample of 75 antiretroviral (ART)-naive African mothers with human immunodeficiency virus infection and their infants. GBV-C RNA was extracted from serum and amplified by reverse-transcriptase polymerase chain reaction. Twenty-seven (36%) of these 75 HIV-infected women tested positive for GBV-C RNA. To study transmission dynamics, we chose a random subsample of 20 of these women and their infants. In this cohort, there was evidence of postnatal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
2
16
1
Order By: Relevance
“…The genotype of GBV-C was not examined though it is reasonable to postulate that they were infected with genotype 1 or 5 isolates, the most prevalent genotypes in Africa [Muerhoff et al, 2005]. Finally, an examination of GBV-C/HIV co-infection among African mothers and their infants from KwaZulu Natal province of South Africa revealed an association between co-infection and protection or delayed disease progression [Sathar et al, 2004]. Based on previous epidemiological data [Tucker et al, 1999;Sathar and York, 2001] it is likely that these individuals were infected with genotype 5.…”
Section: Biological Relevance Of Gbv-c Genotypesmentioning
confidence: 99%
“…The genotype of GBV-C was not examined though it is reasonable to postulate that they were infected with genotype 1 or 5 isolates, the most prevalent genotypes in Africa [Muerhoff et al, 2005]. Finally, an examination of GBV-C/HIV co-infection among African mothers and their infants from KwaZulu Natal province of South Africa revealed an association between co-infection and protection or delayed disease progression [Sathar et al, 2004]. Based on previous epidemiological data [Tucker et al, 1999;Sathar and York, 2001] it is likely that these individuals were infected with genotype 5.…”
Section: Biological Relevance Of Gbv-c Genotypesmentioning
confidence: 99%
“…In that study, researchers also found an intermediate protective role for antibodies specific for the E2 protein of GBV-C. Studies conducted in the highly active antiretroviral therapy (HAART) era have demonstrated that GBV-C is associated with lower rates of HIV rebound after HAART-driven virological success (Antonucci et al 2005, Souza et al 2006. Several mechanisms have been proposed to explain the putative effect of GBV-C on the course of HIV disease, such as increased secretion of the chemokines regulated on activation, normal T cell expressed and secreted (Nattermann et al 2003), macrophage inflammatory protein (MIP)-1α, MIP-1β and stromal cell-derived factor-1, reduced expression of the chemokine receptors CCR5 and CXCR4 (Xiang et al 2004), preservation of the Th1 cytokine profile (Sathar et al 2004), activation of the interferon (IFN) gene system (Capobianchi et al 2006), increased frequency of plasmacytoid dendritic cells expressing CD80 (Lalle et al 2008) and decreased T cell activation (Maidana-Giret et al 2009). In contrast, other studies have failed to demonstrate an influence of GBV-C on the course of HIV infection (Quiros-Roldan et al 2002, Jung et al 2005, Van der Bij et al 2005, Haji Molla Hoseini et al 2007), while at least one report concluded that GBV-C viremia tended to worsen rather than improve mortality among the co-infected patients (Brust et al 2002).…”
mentioning
confidence: 99%
“…Wide variations in rates of MTCT of GBV-C (range, 13%-100%) were reported in 19 published studies that we identified [1,2,4,11,12,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. A limitation of all of these studies is their sample size, varying from 1 to 34 GBV-C-infected women.…”
mentioning
confidence: 99%